Facing the Facts:: Peacekeeping's Place Within a Broader Approach to Security - Fitz-Gerald, Ann (Journal of Conflict Studies, 2005)
ABSTRACT Although the term "peacekeeping" still remains prominent in conceptual and academic circles, its potency as an immediate post-con flict policy instrument has ceased. So too has the effectiveness of a broad multilateral approach to peacekeeping eroded over the years, only to be replaced by more focused efforts to promote regional peacekeeping and bolster the capacity of the regional organizations to undertake peacekeeping operations. While much literature exists on the limitations of conventional UN peacekeeping and the broader operational roles peacekeepers are now expected to take on, far less has been written on the wider security and development policy that operational mechanisms like peacekeeping are now expected to support in most overseas interventions. Understanding the nature of this support is important for appreciating the new time horizons, new partners and new programs to which today's "peacekeepers" contribute. Key to this understanding is also the way in which bilateral and multilateral institutional structures have adapted to the "security-development" agenda and have responded in a more unified and strategic way. This article examines the persisting chal lenges that affect the traditional understanding of peacekeeping and the role of today's international peacekeeping forces. Secondly, it investigates the way in which broader security and development policy has evolved over the past decade, and describes the institutional changes that have emerged within bilateral and multilateral organizations. Lastly, it explores the legal, bureaucratic, and administrative hurdles that continue to challenge the era of "joined-up" government. Conclusions question whether or not, in such a state of organizational incoherence, international peacekeeping can survive as an effective policy instrument.